Pediatric Lyme Disease in Northern Italy: An 18-Year Single-Center Case Series - Forlanini, Federica; Di Tonno, Raffaella; Caiazzo, Roberta; David, Daniela; Valentino, Maria Sole; Rimoldi, Sara Giordana; Zuccotti, Gian Vincenzo; Trevisan, Giusto; Basile, Francesca Wanda; Giacomet, Vania (Microorganisms (Basel), 2024)
Tracing the profile of pediatric Lyme borreliosis (LB) in Europe is difficult due to the interregional variation in its incidence and lack in notifications. Moreover, the identification of LB can be challenging. This study is an 18-year case series of 130 children and adolescents aged under 18 years referred to the Pediatric Infectious Diseases Unit at L. Sacco Hospital, Milan, with suspicion of LB, between January 2005 and July 2023. The routine serological workup consisted of a two-step process: an initial screening test followed by Western blot (WB). Forty-four (34%) patients were diagnosed with LB. The median age was six years, and 45% were females. Of the children with erythema migrans (EM), 33 (57%) were confirmed as having true EM, and, of these, 4 (12%) were atypical. Ten (23%) patients had early disseminated/late diseases, including facial nerve palsy (n = 3), early neuroborreliosis (n = 1), arthritis (n = 3), relapsing fever (n = 2), and borrelial lymphocytoma (n = 1). No asymptomatic infections were documented. Over seventy percent of confirmed LB cases (n = 31/44) recalled a history of tick bites; in this latter group, 19 (61%) were from the area of the Po River valley in Lombardy. Almost half of the children evaluated for LB complained of non-specific symptoms (fatigue, musculoskeletal pain, skin lesions/rash, and persistent headache), but these symptoms were observed in only two patients with confirmed LB. Most LB cases in our study were associated with EM; two-tier testing specificity was high, but we found frequent non-adherence to international recommendations with regard to the timing of serology, application of the two-step algorithm, and antibiotic over-prescription. Most children were initially assessed for a tick bite or a skin lesion suggestive of EM by a family pediatrician, highlighting the importance of improving awareness and knowledge around LB management at the primary healthcare level. Finally, the strengthening of LB surveillance at the national and European levels is necessary.